Photovoltaic charge controller - Noor Juwaina Ayuni, Mohd (2009)
Photovoltaic or in short term PV is one of the renewable energy resources that recently has become broader in nowadays technology. The demand or future work is looking for high efficiency, more reliable and economical price PV charge controller which is come in portable size has become very popular in PV system. In general, PV system consists of a PV array, charge controller, rechargeable battery and dc load. PV charge controller is very important in PV system. In this project, a PV Charge Controller is designed based on microcontroller (PIC 16F877A) which reduced complexity in the number of electronic components and increased monitoring and regulative functions. This project used dc-dc buck converter circuit which has been simulated using software of OrCAD PSPICE. Pulse width modulation (PWM) will be implemented on a PIC 16F877A to control duty cycle, voltage and current in the PV system and is programmed using software of Microcode Studio. Liquid Crystal Display (LCD) is used to display the voltage and current from rechargeable battery. The benefit of this project is an improvement of efficiency depend on duty cycle and voltage change